Legal Aspects of Blockchain Technology Use - Подцерковний, Олег Петрович; Подцерковний, О. П.; Подцерковный, Олег Петрович; Podtserkovnyi, Oleh P.; Podtserkovnyi, Oleg; Santiago, Faisal; Метіль, Анастасія Сергіївна; Метіль, А. С.; Метиль, Анастасия Сергеевна; Metil, Anastasiia S.; Возняковська, Крістіна Анатоліївна; Возняковська, К. А.; et al. (Allied Business Academies, 2019)
The legal regulation of blockchain technology in Ukraine is now in its nascent stage. Legislators are actively working in this direction, but so far there are only bills submitted for consideration by the Verkhovna Rada, or draft bills. Therefore, while using blockchain-based systems, one should be guided by general norms and international standards regarding the scope of activities of blockchain companies. This document should also consider aspects of the activities of various blockchain companies depending on their type of activity. Firstly, we are talking about defining the legal aspects of the activities of mining companies-those that provide functioning of various areas of cryptoeconomics. Secondly, cryptocurrency companies that allows exchanging, selling virtual currencies and creating platforms for cryptocurrency trading. Thirdly, ICO companies-those that attract financing through the Initial Coin Offering. Fourthly, these are companies that offer and provide services and/or goods using blockchain technology.

Правове регулювання технології блокчейн в Україні зараз знаходиться на стадії зародження. Законодавці активно працюють у цьому напрямку, але поки є лише законопроекти, які вносяться на розгляд Верховної Ради. Тому при використанні систем на основі блокчейну слід керуватися загальними нормами та міжнародними стандартами щодо сфери діяльності блокчейн-компаній. У цьому документі також мають бути розглянуті аспекти діяльності різних блокчейн-компаній залежно від їх виду діяльності. По-перше, мова йде про визначення правових аспектів діяльності майнінгових компаній – тих, які забезпечують функціонування різних сфер криптоекономіки. По-друге, криптовалютні компанії, що дозволяють обмінювати, продавати віртуальні валюти та створювати платформи для торгівлі криптовалютою. По-третє, ICO-компанії - ті, що залучають фінансування через первинне розміщення монет. По-четверте, це компанії, які пропонують і надають послуги та/або товари за допомогою технології блокчейн.
Santiago F. Legal Aspects of Blockchain Technology Use / F. Santiago, A. Metil, O. Podtserkovnyi, K. Vozniakovska, V. Oliukha // Journal of Legal, Ethical and Regulatory Issues. - Vol. 22. - Issue 6. - Allied Business Academies, 2019. - P. 1-6.
Keywords: blockchain; cryptocurrency; virtual currency; Initial Coin Offering; mining; блокчейн; криптовалюта; віртуальна валюта; первинне розміщення монет; майнінг; Research Subject Categories::LAW/JURISPRUDENCE